Altered central pain processing in patients with degenerative lumbar diseases and its association with low physical activity levels after lumbar spinal surgeries: a retrospective cohort analysis - Chen, Kaiwen; Nie, Cong; Zhu, Yu; Lyu, Feizhou; Jiang, Jianyuan; Zheng, Chaojun (European spine journal, 2024)
Purpose To investigate the occurrence of altered central pain modulation in patients with degenerative lumbar diseases (DLDs) and to analyze its association with physical activity (PA) 3 years after lumbar decompression and fusion. Methods Preoperative assessments of pressure pain thresholds (PPTs), temporal summation (TS), conditioned pain modulation (CPM) and pain were, respectively, recorded in 304 patients. These patients further underwent International Physical Activity Questionnaire (IPAQ) and both pain-related and psychological assessments 3 years post-operation. Results Preoperatively, the patients had lower PPTs in both local pain and pain-free areas and lower CPM and higher TS in pain-free areas than healthy subjects ( P < 0.05). Postoperatively, 53.9% (164/304) patients showed PA below healthy-related thresholds (< 600 MET min/w). Low PA group showed a greater postoperative weight gain and bone loss and a higher postoperative prevalence of both moderate anxiety and marginal depression than high PA group ( P < 0.05). All covariates with differences between the high and low PA groups were subjected to multivariate logistic regression, and long preoperative disease duration, low preoperative PPT in pain-free area, high preoperative TS, revision surgery, severe postoperative low back pain and significant postoperative pain catastrophizing thought were independently associated with low postoperative PA ( P < 0.05). Conclusions This study supports the existence of central sensitization (CS) caused by abnormal central pain modulation in DLDs. Pre-existing CS in these patients may be associated with low PA after lumbar surgeries, and this low-activity lifestyle may predispose patients to multiple adverse health outcomes. Preoperative dynamic quantitative sensory testing may provide information for the identification of at-risk patients.